Viral driven epigenetic events alter the expression of cancer-related genes in Epstein-Barr-virus naturally infected Burkitt lymphoma cell lines - Hector Hernandez-Vargas (Nature Portfolio, 2017)
Abstract Epstein-Barr virus (EBV) was identified as the first human virus to be associated with a human malignancy, Burkitt’s lymphoma (BL), a pediatric cancer endemic in sub-Saharan Africa. The exact mechanism of how EBV contributes to the process of lymphomagenesis is not fully understood. Recent studies have highlighted a genetic difference between endemic (EBV+) and sporadic (EBV−) BL, with the endemic variant showing a lower somatic mutation load, which suggests the involvement of an alternative virally-driven process of transformation in the pathogenesis of endemic BL. We tested the hypothesis that a global change in DNA methylation may be induced by infection with EBV, possibly thereby accounting for the lower mutation load observed in endemic BL. Our comparative analysis of the methylation profiles of a panel of BL derived cell lines, naturally infected or not with EBV, revealed that the presence of the virus is associated with a specific pattern of DNA methylation resulting in altered expression of cellular genes with a known or potential role in lymphomagenesis. These included ID3, a gene often found to be mutated in sporadic BL. In summary this study provides evidence that EBV may contribute to the pathogenesis of BL through an epigenetic mechanism.